Will graduating year accountancy students cheat in examination? a Malaysian case - Abu Bakar, Nur Barizah; Ismail, Suhaiza; Mamat, Suaniza (Canadian Center of Science and Education, 2010)
Due to a series of high profile accounting scandals and corporate collapses such as Enron, World.Com and Andersen, ethical conduct has been widely recognized as a crucial element in accounting profession and education. The growing concern over the ethics of professionals has also called for more academic research into this critical area. Our study aims at assessing ethical behaviors of the future accounting professionals (i.e. final year accounting students) in Malaysia. This study which uses questionnaire survey examined the students’ ethical attitudes as to whether they would act unethically in an examination. Also, their attitudes towards whistleblowing – if they become aware of such unethical conduct were examined. A vast majority of students (73 per cent), decided to be on the safe side – neither being purely unethical nor whistleblowers. Of the students, 11 per cent chose to become whistleblowers. While only 16 per cent would act unethically in exam, the percentage significantly declined once the risk of being caught was introduced. This indicates that students have not moved further from the first level of Kohlberg’s stages of moral development which highly depends on the punishment and penalty in order to behave ethically. Results also reveal that students with good academic achievement were less likely to cheat in exam. Furthermore, a larger proportion of male students as compared to female tend to behave unethically. Overall, the study indicates favorable results since the majority of respondents would not prefer to indulge in unethical behavior, although they are not being purely ethical.